PENGARUH MODEL TTW (THINK TALK AND WRITE) TERHADAP HASIL BELAJAR KIMIA SISWA PADA MATERI PEMANASAN GLOBAL - Novriza, Novriza; Utami, Lisa (Journal of Chemistry Education and Integration, 2024)
AbstractThe low of student learning achievement was one of obstacles in the learning process.  This research aimed at finding out the effect of Think Talk and Write learning model toward student learning achievement on Global Warming lesson at the tenth grade of State Senior High School 3 Pekanbaru.  Experiment method was used in this research.  It was quasi-experiment with pretest and posttest non-equivalent control group design.  All the tenth-grade students (8 classes) were the population of this research, and the samples were the tenth-grade students of class KM6 as the control group and students of class KM3 as the experiment group.  Random sampling technique was used in this research.  Multiple choice test was the technique of collecting data, and processing the data was done by using t-test and determination coefficient.  In t-test, the result of sig. (2-tailed) 0.000 was lower than 0.05, so H0 was rejected and Ha was accepted.  In determination test, the score of r2 was 0.030, so it could be concluded that Think Talk and Write learning model affected student learning achievement on global warming lesson 3%. Keywords : Effect, Think Talk and Write, Learning Achievement, Global Warming